What can Project Work Achieve in the Asian Teaching Context? - Hans, Lal (INTI International University, 2007)
The advantages of using project work in the English language classroom as a means of promoting learner autonomy, authentic language use, and a learner-centered approach are well-documented. However, in the Asian teaching context project work is often either not used at all or used with limited success. This paper seeks to identify problem areas when using project work in this teaching context, and explore strategies which may help to make the use of project work a more valuable experience for our learners.